Iron: an essential micronutrient for the legume-rhizobium symbiosis - Brear, Ella M.; Day, David A.; Smith, Penelope M. (Frontiers in Plant Science, 2013)
Legumes, which develop a symbiosis with nitrogen fixing bacteria, have an increased demand for iron. Iron is required for the synthesis of iron-containing proteins in the host, including the highly abundant leghemoglobin, and in bacteroids for nitrogenase and cytochromes of the electron transport chain. Deficiencies in iron can affect initiation and development of the nodule. Within root cells, iron is chelated with organic acids such as citrate and nicotianamine and distributed to other parts of the plant. Transport to the nitrogen-fixing bacteroids in infected cells of nodules is more complicated. Formation of the symbiosis results in bacteroids internalized within root cortical cells of the legume where they are surrounded by a plant derived membrane termed the symbiosome membrane (SM). This membrane forms an interface that regulates nutrient supply to the bacteroid. Consequently, iron must cross this membrane before being supplied to the bacteroid. Iron is transported across the symbiosome membrane as both ferric and ferrous iron. However uptake of Fe(II) by both the symbiosome and bacteroid is faster than Fe(III) uptake. Members of more than one protein family may be responsible for Fe(II) transport across the SM. The only Fe(II) transporter in nodules characterized to date is GmDMT1, which is located on the symbiosome membrane in soybean. Like the root plasma membrane, the symbiosome membrane has ferric iron reductase activity. The protein responsible has not been identified but is predicted to reduce ferric iron accumulated in the symbiosome space prior to uptake by the bacteroid. With the recent publication of a number of legume genomes including Medicago truncatula and Glycine max, a large number of additional candidate transport proteins have been identified. Members of the NRAMP, YSL, VIT and ZIP transport families show enhanced expression in nodules and are expected to play a role in the transport of iron and other metals across symbiotic membranes.